Characterization of Atrazine-Loaded Biodegradable Poly(Hydroxybutyrate-Co-Hydroxyvalerate) Microspheres - Grillo, Renato [UNESP]; Melo, Nathalie F. S. de [UNESP]; Lima, Renata de; Lourenço, Roberto Wagner [UNESP]; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Springer/plenum Publishers, 2010)
Polyhydroxybutyrate-co-hydroxyvalerate microspheres (PHBV-MS) were prepared as a delivery system for the herbicide atrazine (ATZ). Characterization of the system included investigation of in vitro release properties and genotoxicity. ATZ - PHBV-MS particle diameters showed a size distribution range of 1-13 mu m. Differential scanning calorimetry analyses indicated that ATZ was associated with the PHBV microparticles. The release profiles showed a different release behavior for the pure herbicide in solution, as compared with that containing ATZ-loaded PHBV-MS. Korsmeyer-Peppas model analyses showed that atrazine release from the microparticles occurred by a combination of diffusion through the matrix and partial diffusion through water-filled pores of the PHBV microparticles. A Lactuca sativa test result showed that the genotoxicity of ATZ-loaded PHBV-MP was decreased in relation to ATZ alone. The results demonstrate a viable biodegradable herbicide release system using atrazine for agrochemical purposes.
Keywords: Atrazine; Pesticide; PHBV; Microspheres; Release system